2019
DOI: 10.1037/pla0000096
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of child-centered play therapy among marginalized children.

Abstract: Marginalized children are often excluded from mainstream social, economic, cultural, and political life because of ethnicity or poverty. These children are more likely to have behavior problems that place them at risk later in life. The impact is evident at an early age. The purpose of this article was to review the literature that examined the impact of child-centered play therapy (CCPT) conducted with marginalized children. The literature was reviewed with regard to the results of the studies, the outcome va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…The body of play literature strongly supports the importance of addressing multicultural issues and identifying culturally relevant treatments for diverse child populations (Baggerly & Parker, 2005; Ceballos et al, 2012; Post et al, 2019). Although no experimental play therapy studies have explored the use of CCPT exclusively with African American children, studies with the inclusion of African children have shown promise.…”
Section: Child-centered Play Therapymentioning
confidence: 99%
“…The body of play literature strongly supports the importance of addressing multicultural issues and identifying culturally relevant treatments for diverse child populations (Baggerly & Parker, 2005; Ceballos et al, 2012; Post et al, 2019). Although no experimental play therapy studies have explored the use of CCPT exclusively with African American children, studies with the inclusion of African children have shown promise.…”
Section: Child-centered Play Therapymentioning
confidence: 99%
“…Despite the dominance of highly intellectualised neurological theories in research in the trauma field, we chose to privilege experiential knowing as potentially leading to novel discoveries that have greater relevance for practice. Given the effectiveness of play-based methods with marginalised young people ( Post et al, 2019 ), we selected research methods that enabled multiple ways of communicating how satisfied the young people were with the programs. By integrating non-verbal feedback, we were able to draw on our practice experiences as music therapists who grapple regularly with the challenges of interpreting arts-based and behavioural responses as an equally interesting way of understanding phenomena ( Chamberlain et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…According to Wang et al ( 2020 ), the closure of schools upon the COVID-19 pandemic, the physical and mental health of 180 million primary and middle school children and 47 million preschool children could potentially be adversely affected, due to less physical activity, long-term screen viewing, irregular sleep, unsuitable diets, and weight gain. However, play has a therapeutic power (Chazan & Cohen, 2010 ; Post et al, 2019 ) and is known to survive not only through destructive social events, such as war and terrorism (Feldman, 2019 ; Paksuniemi et al, 2015 ) but also in natural disasters (Kousky, 2016 ). In this context, although the healthy development of play identity is affected by negative social events or natural disasters, the healing power of play within its own dynamics is considered to have the potential to treat the damage that might occur in play identity.…”
Section: Discussionmentioning
confidence: 99%
“…Immigrant children experience mental and physical health problems in the countries they have moved to, showing developmental disorders under stress, and frequently experiencing traumas due to the need to adapt to a different society (Ehntholt & Yule, 2006 ). Children who are excluded from social, cultural, economic, and political life due to their ethnic identity or poverty have the potential to exhibit behavioral problems at later stages in their lives (Post et al, 2019 ). In another study on the effect of ethnicity and immigration on the choice of play and toys, it was reported that the quality of toy choices and playing times of children aged three to four years varied according to socio-economic status, ethnicity, and gender (Trawick-Smith et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%